Pengaruh Total Quality Control (TQC) dan Total Quality Management (TQM) Terhadap Kinerja Karyawan pada Penerapan Keselamatan dan Kesehatan Kerja (K3) Sebagai Mediasi: Studi pada Pekerja Bagian Produksi PT. Metal Hitech Engineering - Annisa Fadhilah; Abi Hanif Dzulqarnain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Occupational Safety and Health (K3) has an important role in improving employee performance, especially in the manufacturing industry. This study aims to analyze the effect of Total Quality Control (TQC) and Total Quality Management (TQM) on employee performance with OHS as a mediating variable at PT Metal Hitech Engineering. The research method used is quantitative with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The sample of this study amounted to 57 employees from the production department with saturated sample technique. The results showed that TQC and TQM have a significant influence on employee performance, both directly and through K3 mediation. Optimal OHS implementation can improve employee welfare and productivity, so companies need to develop strategies such as periodic training, improving safety standards, and optimizing the quality management system. These findings are expected to be a reference for companies in implementing more effective K3 policies to improve company performance and competitiveness.